(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: - To study the prevailing trends of suicide in Pakistan. Study Design: Retrospective study Setting: Services Hospital, Lahore, Sir Gangaram Hospital ,Lahore, Banzeer DHQ Hospital, Abbottabad. Duration of study: 01-01-2012 to 30-09-2013 Materials & Methods: The socio-demographic profile of 100 cases of suicide was recorded. Results: There were 63 % males and 37 % in females. The most vulnerable age to commit suicide was 21 – 30 years (26 %) and afterward there was decline in the tendency, 25 % at the age of 31 – 40 years, 20 % at the age of 41 – 50 years, 17 % at the age of 51 – 60 years, 5 % at the age of 61 – 70 years and zero percent at the age of 71. The suicidal tendency was maximum in laborers and factory workers (27 %) and minimum in businessman (0.2 %), more in rural population (39 %) than in urban population, more in illiterate persons 53 % as compared to literate persons (47 %), more in lower socio-economic class (49%) than upper class(14%) and more in addicts (62 %) than non addicts (38 %). The maximum victims committed% suicide with fire arm weapon and burning (27 % each) followed by hanging 15 %, bomb blast 13 %, drowning 07 %, suicidal jacket and poisoning 04 %, electric current 03 %. Conclusions and Recommendations: The suicidal trends are at rise national as well as internationally. The contributory factors are a illiteracy, poverty, addictions, frustrations in life. It is recommended that social services in the society should be improved in the form of counseling of depressed persons. It will minimize the suicidal tendencies.